Antioxidant Synergisms between Cymbopogon citratus Polyphenols and a-Tocopherol in DPPH Radical-Scavenging Assay - Bao, Xiao-Li; Yuan, Hui-Hui; Zhao, Hong-Li; Fang, Xue-Xiang; Sun, Bo; Lan, Min-Bo (Asian Journal of Chemistry, 2015)
The synergistic antioxidant effects of polyphenols obtained from Cymbopogon citratus Stapf (Gramineae) by bioassay-guided fractionation, including caffeic acid, chlorogenic acid, isoorientin 2''-O-rhamnoside and isoorientin, with a-tocopherol were studied using DPPH (1,1-diphenyl-2-picrylhydrazyl) radical-scavenging assay. Combination index (CI) and isobolographic analyses were employed to detect any inducement of the antioxidant activity compared with the individual activities of polyphenols and a-tocopherol. The reaction kinetics were studied by monitoring the consumption of DPPH•, a-tocopherol and C. citratus polyphenols. It was found that synergisms could occur between the four respective C. citratus polyphenols and a-tocopherol in the radical-scavenging assay, which were dependent on the antioxidants involved and their ratios in the mixtures. Kinetic studies on the antioxidation process revealed that these synergistic effects were associated with the sparing effects of C. citratus polyphenols on a-tocopherol, which have been ascribed to the regeneration of a-tocopherol by the polyphenols.